A patient-centric approach to improve health care services - Isaac Pergher; Vanessa Patzlaff Brandolf; Diego Augusto de Jesus Pacheco; Guilherme Luís Roehe Vaccaro (Cogent Business & Management, 2016)
This research proposes a diagnostics and improvement approach based on Total Quality Management to apply in cancer health care services systems. The proposed approach adopts the integrated use of process failure mode and effects analysis (PFMEA) and the current reality tree (CRT) from the Theory of Constraints Thinking Process. The utilization of those methodologies explores the strengths of each approach and it was implemented in two steps. Initially, CRT was built targeting the identification of the primary causes of low speed of service and the secondary elements that form the link between the focal problem and the primary causes. Next, the CRT data were utilized to create the PFMEA. To analyze the proposed model, a case study was applied in the radiotherapy service authorization process in a large Brazilian hospital. The main results permitted the definition of a set of actions to eliminate or reduce the failure modes in health care systems. In addition to that, one of the advantages of the approach proposed and applied is the identification of the root causes (RC) of the problem in flow management of patients, the undesirable effects of these causes and the prioritization of the improvement actions. The approach enables managers and decision-makers in health care systems to identify the global RC of problems and the prioritization of actions. The overall pattern of findings suggests that integration of PFMEA and CRT creates several benefits to increase the velocity of service to patient being treated for cancer in health care systems. Decision-makers can apply the approach to improve the velocity and the flow management of patients.